Establishment of the Faculty of Veterinary Medicine at University Malaysia Kelantan - Mohd Azam Khan Goriman Khan; Imad Ibrahim Ali Al-Sultan; Jasbir.S; Ibrahim Che Omar; Ali Reza Badiei (2010)
Universiti Malaysia Kelantan (UMK) is the second university to offer the professional veterinary medicine programme in Malaysia. The Faculty of Veterinary Medicine (FPV) is the fourth faculty in UMK and was established in line with the 9th Malaysia Plan and the 2nd and 3rd National Agricultural Policies (NAP 1992-2010) which emphasised on developing the animal industry and agriculture to increase the country’s economy. Currently, the faculty is located in Pengkalan Chepa, Kota Bharu but the permanent site is expected to be ready in Jeli by the last quarter of 2011. The faculty was established on the 29th June, 2009 with an enrolment of 39 students, and it envisages being one of the leading veterinary schools in Southeast Asia. A second batch of students will enroll in July 2010. The curriculum consists of biomedical and veterinary subjects as well as preclinical and clinical subjects. The students will also have four courses of clinical practice and will need to undergo industrial training in private and government farms between the semesters of each year to strengthen their learning skills and apply the knowledge that they have learnt from their lectures. The establishment of FPV is considered timely for numerous reasons, among which include the strategic location of UMK in the east coast of the Peninsula, being at the heart of the ruminant livestock sector which is one of the fastest growing agriculture industries in the region. Since UMK is the secretariat for the East Coast Economic Region (ECER) under MOHE, FPV is expected to play a significant role in catalysing the development of the animal industry through active participation in research and consultancy services. These efforts are greatly needed to enable the country to achieve self sufficiency in beef, mutton and dairy products. An important advantage is its location in the state renowned for its entrepreneurial people. The tagline “Entrepreneurship is our thrust” is emphasised in the curriculum so as to develop entrepreneurship among veterinarians. To do this, the components of the curriculum on industrial training and business management are included and enhanced. Students will spend more time in animal related industries during their semester breaks to provide them ample experiences and knowledge in establishing their own entrepreneurial business upon graduation. The thrust will be to use animal science and technology with entrepreneurship for the creation of wealth. Students will also be taught to acquire analytical, critical, creative, innovative and leadership qualities to ensure their competitiveness in the job market. This will ensure human capital par excellence ready to face contemporary challenges in the future. Our mission is to improve animal and human health and well being and contribute to the Malaysian economy and beyond through the provision of innovative learning experiences and infusion of entrepreneurial and leadership skills within the veterinary curriculum, engagement of faculty in research and scholarly activities, advancement and communication of knowledge, the provision of professional services and smart partnerships with the community. With the present strength of 7 pioneer academic staff, the faculty also offers MSc and PhD degrees by research. More lecturers are expected to join the faculty soon including experts from the Department of Veterinary Services (DVS) Malaysia, Universiti Putra Malaysia (UPM) and MARDI to share their experiences with the students through talks and seminars. Frequent field trips will be organised to government agencies and private animal industries to provide relevant knowledge to the students. A memorandum of understanding (MOU) with DVS was signed on the 16th of August, 2009 to share facilities needed for teaching. The faculty aims to produce veterinary graduates who will make positive impacts on food animal production and farm community development, producing human capital that will play a major role as guardians of our nation's food supply in both health and safety perspective. The faculty plans to work with our ASEAN neighbours to encourage student mobility for their veterinary programme, enabling the students to experience veterinary education and neighbouring culture without losing time in their tight schedule. Academic staff mobility will also be encouraged with our counterparts so they will continue to learn and enrich ourselves to provide quality veterinary education in this region. It is hoped that the fraternity will share this vision, and be a beacon of hope for our students, community and “all creatures big and small”.